Comprehensive evaluation of water resources security of the Huaihe Eco-economic Belt. Issue 1 (6th July 2021) - Ruan, Jun; He, Gang
Abstract: The study of water resource security is a basic scientific issue that must be faced in the construction of the ecological environment. To examine the status of regional water resources security in the Huaihe Eco-economic Belt, this study builds a comprehensive evaluation index system based on the 'Driving-Pressure-State-Impact-Response' (DPSIR) framework, combines the entropy weight method and Lotka–Volterra symbiosis model to calculate the water resources security status from 2010 to 2018. Then the fixed effects regression model is used to analyze the factors affecting the water resources system. The results show that: (1) The status of water resources security in the Huaihe Eco-economic belt decreased from 2011 to 2017 and, thereby transitioned from a safe to a dangerous state. The coordination index of the economic system and water resource system was only −0.17 in 2017, and the partial development model benefited the economy but damaged the water resources. (2) The security status of 25 prefecture-level cities improved significantly, and the number of cities with status of alert or above increased from 11 to 15. However, there are apparent differences among the regions. The status has shifted to 'north and south being better than east and west'. The water resources security status of Jining, Linyi, and Lu'an have improved, whereas Yancheng, Taizhou, Pingdingshan, and other cities showed rather poor development during 2017. (3) The correlation coefficient of the economic system was −0.154 and hindered the development of the water resources system. The correlation coefficients of the added value of the tertiary industry and the expenditure on energy conservation and environmental protection was 0.699 and 0.180 respectively and played a positive role in promoting the water resources system. It is necessary to optimize and adjust the industrial structure and protect the environment. HIGHLIGHT: The Lotka–Volterra symbiosis model is introduced to the paper and has good applicability in water resources security research. The Huaihe Eco-economic Belt is taken as the research area and the empirical results are conducive to promoting the development and implementation of national strategies. ArcGIS software is used to visualize the results and the dynamic change of water resources security status.